Toxicity Effect of Colloidal Silver Nanoparticles to Marine Microalgae, Nannochloropsis oculata - Seyed Ali Johari; Zhila GhaderSarbaz; Iman Sourinejad (بوم‌شناسی آبزیان, 2016)
To assess the acute toxicity of colloidal silver nanoparticles (AgNPs) in Nannochloropsis oculata, microalgal cells were exposed to different concentrations of AgNPs for 72 hours and according to OECD 201. Algal cell count was done every 24 hours and average specific growth rate, as well as percent inhibition of the average specific growth rate, were calculated for each concentration. Also, the amount of inhibitory concentrations (IC) and median inhibitory concentration (IC50) of this nanomaterial were calculated according to the percent inhibition of the average specific growth rates and by using the Probit Analysis program. The results showed that even at the lowest concentration (0.005 mg/L), silver nanoparticles reduced the growth of Nannochloropsis microalgae. Accordingly, No Observed Effect Concentration (NOEC), Lowest Observed Effect Concentration (LOEC), and IC50 of this nanomaterial for tested microalgae were 0.001, 0.005, and 0.036 ± 0.009 mg/L. On this basis, and considering the Globally Harmonized System of Classification and Labelling of Chemicals (GHS), tested AgNPs are classified as “category acute 1” or “very highly toxic” for N. oculata, so any accidental or intentional release of AgNPs containing wastewaters to aquatic ecosystems may cause irreparable effects on the aquatic environment.